2020
DOI: 10.1021/acs.inorgchem.0c01938
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Mononuclear Pd(I) Complexes Supported by N2S2 and N4 Tetradentate Ligands

Abstract: Palladium is a versatile transition metal used to catalyze a large number of chemical transformations, largely due to its ability to access various oxidation states (0, I, II, III, and IV). Among these oxidation states, Pd(I) is arguably the least studied, and while dinuclear Pd(I) complexes are more common, mononuclear Pd(I) species are very rare. Reported herein are spectroscopic studies of a series of Pd(I) intermediates generated by the chemical reduction at low temperatures of Pd(II) precursors supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 65 publications
2
42
0
1
Order By: Relevance
“…12-14 While higher oxidation states (Pd 6+ ) have been reported in organometallic complexes, 19 Pd + and Pd 3+ compounds are exceedingly rare. Pd + had only been observed in a small number of binuclear Pd complexes, 20 until a family of mononuclear Pd + species was very recently characterized by Luo et al 21 In the zeolite literature, Jacquemin et al have reported the presence of Pd + cations based on observation of EPR signals consistent with the presence of paramagnetic species in their study of the catalytic properties of Pd and Fe-exchanged beta zeolites for toluene oxidation. 22 In a recent study, Paolucci et al assessed the speciation of Pd in zeolites under PNA conditions using both experiments and periodic DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…12-14 While higher oxidation states (Pd 6+ ) have been reported in organometallic complexes, 19 Pd + and Pd 3+ compounds are exceedingly rare. Pd + had only been observed in a small number of binuclear Pd complexes, 20 until a family of mononuclear Pd + species was very recently characterized by Luo et al 21 In the zeolite literature, Jacquemin et al have reported the presence of Pd + cations based on observation of EPR signals consistent with the presence of paramagnetic species in their study of the catalytic properties of Pd and Fe-exchanged beta zeolites for toluene oxidation. 22 In a recent study, Paolucci et al assessed the speciation of Pd in zeolites under PNA conditions using both experiments and periodic DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…37 In our previous study, we were able to fully characterize the Pd I dinuclear complex [(N2S2)Pd I (µ-tBuNC)]2(ClO4)2. 30 While in this Pd I dinuclear complex the N2S2 ligand interacts with the Pd center through only one Pd-S bond, the NXS2 ligands (X = N or CH) in the mononuclear complexes Pd-1 and Pd-2 have both S atoms bind to the Pd center. Interestingly, given the presence of the two S soft donors, we were able to observe what is to the best of our knowledge the first four-coordinate, mononuclear Pd I complexes with an unambiguous +1 oxidation state at the Pd center.…”
Section: Main Textmentioning
confidence: 92%
“…[1][2][3][4] In these systems, while the general reaction mechanism involves a Pd 0 /Pd II catalytic cycle, 1,5 several reports proposed the involvement of Pd I intermediates. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Additionally, while there are many examples of transient Pd I species [23][24][25][26][27][28][29][30] as well as isolated Pd I dimers, [31][32][33][34] there are very few examples of well-established monomeric Pd complexes bearing a formal +1 oxidation state at Pd. To the best of our knowledge, only two structurally characterized examples of isolated Pd I complexes -the cationic [Pd I (P t Bu3)2] + species and the [Pd I (MeCN)(P t Bu3)2] + complex, have been reported independently by Chaplin's and Ozerov's groups, respectively.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mononuclear Pd(I) species reported to date are exceedingly reactive and have only been observed using spectroscopic methods in γ-ray irradiated Pd(II)Cl2 and Pd(II)(acac)2 and thermalized Pd(II)-exchanged zeolites (12)(13)(14), where their stability is conferred by immobilization within the lattice framework. Certain Pd(0) and Pd(II) complexes are reported to undergo chemical and electrochemical redox reactions to produce mononuclear paramagnetic Pd(I) complexes (15)(16)(17)(18)(19). These include three isolable complexes [(PBu t…”
mentioning
confidence: 99%